2020
DOI: 10.3892/ol.2020.11282
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of extracellular vesicle microRNA‑101 derived from bone marrow mesenchymal stromal cells in myelodysplastic syndrome with disease progression

Abstract: To evaluate the mechanism underlying the communication between myeloid malignant and bone marrow (BM) microenvironment cells in disease progression, the current study established BM mesenchymal stromal cells (MSCs) and assessed extracellular vesicle (EV) microRNA (miR) expression in 22 patients with myelodysplastic syndrome (MDS) and 7 patients with acute myeloid leukemia and myelodysplasia-related changes (AML/MRC). Patients with MDS were separated into two categories based on the revised International Progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The authors also showed that these EVs could be taken up by healthy CD34+ cells inducing alterations in the expression of MDM2 and TP53 in these cells and in their clonogenicity [ 118 ]. It was also reported that the expression of miR-101 was downregulated in EVs derived from mesenchymal stromal cells from patients with high-risk MDS and acute myeloid leukemia compared to patients with low-risk disease [ 119 ]. Of note, miR-101 suppresses cell proliferation [ 119 ] suggesting that its downregulation could be implicated in the acceleration of MDS cell proliferation and transformation to acute leukemia.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also showed that these EVs could be taken up by healthy CD34+ cells inducing alterations in the expression of MDM2 and TP53 in these cells and in their clonogenicity [ 118 ]. It was also reported that the expression of miR-101 was downregulated in EVs derived from mesenchymal stromal cells from patients with high-risk MDS and acute myeloid leukemia compared to patients with low-risk disease [ 119 ]. Of note, miR-101 suppresses cell proliferation [ 119 ] suggesting that its downregulation could be implicated in the acceleration of MDS cell proliferation and transformation to acute leukemia.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…It was also reported that the expression of miR-101 was downregulated in EVs derived from mesenchymal stromal cells from patients with high-risk MDS and acute myeloid leukemia compared to patients with low-risk disease [ 119 ]. Of note, miR-101 suppresses cell proliferation [ 119 ] suggesting that its downregulation could be implicated in the acceleration of MDS cell proliferation and transformation to acute leukemia. Finally, Meunier et al recently found that small EVs from mesenchymal stromal cells derived from MDS patients induce ROS production promoting DNA damage and mutagenesis in healthy HSC via miRNA transfer [ 120 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…A prognostic significance of EV-microRNAs has also been confirmed in several other hematological malignancies. Saito et al observed a different EV-microRNA expression in subjects with myelodysplastic syndrome and acute myeloid leukemia during disease progression [ 119 ]. EVs might also have a prominent role in MM onset and progression by controlling endothelial cell functions, augmenting tumor cell growth, and increasing immunosuppression [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%